Flexural strength of PVD coated float glass for architectural applications - Meszaros, Robert; Wild, Michael; Merle, Benoit; Wondraczek, Lothar (Glass Technology-European Journal of Glass Science and Technology Part A, 2011)
The effect of PVD coatings on the ring-on-ring flexural strength of soda lime silica float glass was studied. A 70% increase from 280 +/- 8 to 478 +/- 10 MPa was observed on the air-side of the glass after applying a multilayer low emissivity coating of 100 nm total thickness. A similar but less pronounced effect could be obtained with a TiO(2) single layer of 50 nm. At the same time, for both coatings, the Weibull modulus was found to approximately double. Results are interpreted on the basis of two assumptions: initial defects on the glass surface are covered by the coating, and their growth is prevented due to the protective function of the coating, especially as a humidity barrier. Both assumptions were confirmed by atomic force microscopy and micromechanical analyses. This barrier function leads to significantly improved resistance to long term fatigue and stress corrosion, respectively.